2015
DOI: 10.1093/database/bav086
|View full text |Cite
|
Sign up to set email alerts
|

FARE-CAFE: a database of functional and regulatory elements of cancer-associated fusion events

Abstract: Chromosomal translocation (CT) is of enormous clinical interest because this disorder is associated with various major solid tumors and leukemia. A tumor-specific fusion gene event may occur when a translocation joins two separate genes. Currently, various CT databases provide information about fusion genes and their genomic elements. However, no database of the roles of fusion genes, in terms of essential functional and regulatory elements in oncogenesis, is available. FARE-CAFE is a unique combination of CTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…A study of intrinsic disorder in fusion proteins found that translocated proteins are more intrinsically disordered and tend to have fewer Pfam domains than non-translocated proteins ( 87 ) (Figure 3B ), which has recently been demonstrated again ( 88 ). However, another survey of fusion proteins showed that they contain complete protein domains much more frequently than would be expected if fusion transcripts were generated from randomly fused protein coding sequences ( 89 ).…”
Section: Data-intensive Computational Studies Of Gene Fusion Functionmentioning
confidence: 58%
See 2 more Smart Citations
“…A study of intrinsic disorder in fusion proteins found that translocated proteins are more intrinsically disordered and tend to have fewer Pfam domains than non-translocated proteins ( 87 ) (Figure 3B ), which has recently been demonstrated again ( 88 ). However, another survey of fusion proteins showed that they contain complete protein domains much more frequently than would be expected if fusion transcripts were generated from randomly fused protein coding sequences ( 89 ).…”
Section: Data-intensive Computational Studies Of Gene Fusion Functionmentioning
confidence: 58%
“…The most recent gene fusion databases include ChiTaRS 2.1 ( 183 , 184 ), FusionCancer ( 168 ), the TCGA Fusion Portal ( 10 ) and FARE-CAFE ( 88 ). The ChiTaRS 2.1 database of fusion transcripts and RNA-seq data ( 184 ) is the largest fusion databases and one of the few containing non-human fusion data.…”
Section: Detecting Prioritizing and Organizing Oncogenic Gene Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Publicly available fusion gene databases were searched, including The Cancer Genome Atlas (TCGA) fusion gene database (www.tumorfusions.org/) (5), ChiTaRS 3.1 (http:// chitars.md.biu.ac.il/index.html) (17), and FARE-CAFÉ (18).…”
Section: Searching For the Lmo7-braf Fusion Gene In Gene Fusion Databmentioning
confidence: 99%
“…Several databases have been developed that focus on information about fusion genes, their functional role, clinical association and inferred chromosomal breakpoints. Some of these databases are ChimerDB 3.0 (5 Jan 2018) (includes ChimerKB, ChimerSEQ and ChimerPUB) [ 3 ], TicDB Release 3.3 (2 Jan 2017) [ 4 ], COSMIC v83 (4 Jan 2018) [ 5 ], ChiTaRs Version 2.1 (2 Jan 2017) [ 6 ], FARE-CAFÉ (2 Jan 2017) [ 7 ], FusionCancer (3 Mar 2017) [ 8 ], Tumor Fusion Portal (4 Jan 2018) [ 9 ] and ConjoinG (3 Mar 2017) [ 10 ]. In addition to above databases, some other independent datasets are available in literature which provide list of validated fusion genes ( Fig 1 and Table 1 ).…”
Section: Introductionmentioning
confidence: 99%